AB0888 Childhood Arthritis as The First Manifestation of Inflammatory Bowel Disease. (15th July 2016) - Bittermann, V.; Quesada-Masachs, E.; Remesal, A.; Murias, S.; Modesto, C.
Abstract : Background: Joint involvement is the most common extraintestinal manifestation in children with inflammatory bowel disease and it may appear years before its diagnosis. Objectives: To describe the characteristics of arthritis associated with inflammatory bowel disease (IBD) in children. Methods: A retrospective, cross sectional, descriptive study was performed including patients of two Pediatric Rheumatology Units from tertiary hospitals with arthritis as the first manifestation of an inflammatory bowel disease. Results: Data for all JIA patients controlled in 2 tertiary centers were analyzed. 14 patients met the inclusion criteria (10 females/4 males). Median age of onset of joint manifestation was 7 years (3–14.3 years). Median age of onset of gastrointestinal symptoms was 17.1 years (8.8–29.8 years). Musculoskeletal manifestations preceded the intestinal manifestations about 12 years (0.3–21.8 years). Most frequent JIA subtype was extended/persistent oligoarticular form (36% of all cases). Polyarticular type of JIA was present in 3 patient, enthesitis related arthritis in 2 patients and undifferentiated JIA in 2 patients. One patient had reactive arthritis. The most common type of IBD was Crohn's disease (60%). The most frequently affected joint was the knee (57%). In 2 patients the initial affected joint was the hip. ANA were positive in 6 children (40%) and 3 had HLA B27 positive (20%). Fecal calprotectin was normal in 10 patients studied. All patients have received systemic corticosteroids and 70% needed articular infiltration. 85% of patients required biological treatment to control the articular symptoms and/or gastrointestinal (mostly adalimumab) associated with DMARDs in a high percentage. Conclusions: It isn't common that the joint involvement precede the digestive symptoms in IBD. In our series the most frequent category was the oligoarticular form with negative ANA and this presented later than usual. They present an evolution with difficult control of the flares. A large number of patients needed biological treatment to control the articular manifestations. These results support the need for new biomarkers that could detect subclinical intestinal disease in children. Disclosure of Interest: None declared